The Moderation Effect of Role Ambiguity in Relationship of Role Conflict and Occupational Stress After Covid-19 - Farradinna Syarifah; Soraya Nadia; Laila Meiliyandrie Indah Wardani; Wella Jayanti (Universitas Pendidikan Ganesha, 2023)
Due to the worldwide pandemic students is provided with the opportunity to work from home. Several job categories allow direct work from home. This study tries to analyze the work stress, role conflict, and ambiguity experienced by teachers due to Covid-19, as a result of implementing online learning and switching to offline learning when female teachers have a home and work obligations. This study is using a quantitative approach study with moderated correlation analysis. High school teachers from different schools who were women took part in this study. In order to test the research hypothesis, the study looked at the validity of the 175 questionnaires that female teachers had filled out. Data analysis is using PROCESS V4.0. According to this study, the relationship between role conflict and work stress is moderated by role ambiguity, which suggests that changes in teaching affect roles as teachers and households. According to this study, the greater a teacher's role conflict and ambiguity, the greater the risk of work stress.